2014
DOI: 10.1080/10919392.2014.956592
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Demand: Online Music Piracy, Physical Music Sales, and Digital Music Sales

Abstract: Traditionally, music has been sold to consumers by recording several individual songs/tracks in physical media such as CDs and cassettes. Sales of such physical music have been declining for the past several years. Many academic studies have attributed the decline of physical music sales to online music piracy, yet some other studies have not found evidence to support a negative relationship between online music piracy and physical music sales. Interestingly and importantly, we have observed that while many of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Similarly, Danaher et al (2014) found that when the price of popular single songs rose, their sales declined, whereas album sales, a substitute, increased. Following these and other studies, we expect that the commercialization and growth of music streaming platforms, a substitute of physical CDs and downloading music, anticipated a lower demand for CDs and music piracy (European Union News, 2016;Hampton-Sosa, 2017;Koh et al, 2014). Rather than paying the accumulated cost of equivalent physical CDs or the total cost in time to acquire the same amount of music through illegal digital downloading, a consumer may prefer a music streaming subscription that includes access to a large repertoire of music that is both online and offline, devoid of advertisement, and ondemand.…”
Section: Music Piracy and Streaming: Substitutes Or Complementsmentioning
confidence: 83%
“…Similarly, Danaher et al (2014) found that when the price of popular single songs rose, their sales declined, whereas album sales, a substitute, increased. Following these and other studies, we expect that the commercialization and growth of music streaming platforms, a substitute of physical CDs and downloading music, anticipated a lower demand for CDs and music piracy (European Union News, 2016;Hampton-Sosa, 2017;Koh et al, 2014). Rather than paying the accumulated cost of equivalent physical CDs or the total cost in time to acquire the same amount of music through illegal digital downloading, a consumer may prefer a music streaming subscription that includes access to a large repertoire of music that is both online and offline, devoid of advertisement, and ondemand.…”
Section: Music Piracy and Streaming: Substitutes Or Complementsmentioning
confidence: 83%
“…In the music industry, Dörr's research (2013) suggested reduced cost of search and prevention of moral scruples (conscience) as the main influence in OMSS subscription. Koh et al (2014) in their research defined Online Music Piracy as the illegal duplication and distribution of sound or music recordings. It includes peer-to-peer file sharing and recording music from the Internet platforms such as YouTube or Pandora.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A contrasting effect highlights how consumers typically prefer singles rather than full CDs (Mooney et al, 2010) and thus only pirate top of the chart hits Strumpf, 2007, 2010). In addition, the literature highlights how other factors beyond file sharing, such as high album prices, income, music quality, and new, legal, music distribution options (i.e., iTunes-like online stores) could have contributed to the reduction of physical CD sales (Liebowitz, 2006;Koh et al, 2014). Prior research has also underlined the almost 'positive' effects of file sharing such as consumers' increased willingness to pay for original content after the "anticipation effect" generated by online piracy; and the fact that authors' creativity has not been undermined given that the amount of music, books and movies has strongly increased in the last decade (Oberolzer-Gee and Strumpf, 2010).…”
Section: The Internet Revolution Online Piracy and The Music Industrymentioning
confidence: 99%